Clinical management and prevention of dental caries in athletes: A four-year randomized controlled clinical trial. Issue 1 (December 2018) - Frese, C.; Wohlrab, T.; Sheng, L.; Kieser, M.; Krisam, J.; Frese, F.; Wolff, D.
Abstract The aims of this four-year randomized controlled clinical trial were to gain insights into management and prevention of dental caries and the effect of stannous fluoride products in athletes. Fifty-four participants were randomized into test and control groups. The test group used special stannous fluoride products. The primary endpoint dental caries was assessed by the ICDAS-II-System and analyzed both by a linear mixed model for repeated measures and a generalized linear mixed model. During the observation period an increase in caries-free surfaces from 64.91 ± 6.42 at baseline to 73.22 ± 4.43 was observed. In surfaces with caries superficialis and caries media, a decrease from 13.94 ± 5.70 and 2.96 ± 2.55 surfaces at baseline to 7.89 ± 3.18 and 0.46 ± 0.78 after 2.5 years was noted, respectively. The analysis showed no effect of stannous fluoride products, but a significant difference for the time of examination (p < 0.0001). In addition, it could be shown that at any time of examination, the odds of developing caries media on a new surface was significantly lower than at baseline (up to 25-times). Due to biannual dental examinations, professional tooth cleaning and restorative treatment the number of caries-free surfaces increased and the odds of a new surface to be afflicted with caries media decreased 25-fold.